2016
DOI: 10.2217/imt-2016-0068
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Microcrystalline Tyrosine-Adsorbed, Mite-Allergoid Subcutaneous Immunotherapy: 1-Year Follow-Up Report

Abstract: Significant decreases in clinical symptoms and immunological parameters were observed, accompanying a high level of patient satisfaction and tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 13 publications
2
20
0
Order By: Relevance
“…This depot formulation induced an early immunological response, confirmed by statistically significant increments of sIgG and sIgG4 levels against DPT and DF, after approximately 3 months of therapy. Similar results could be observed in other studies, where a fast increase in sIgG and sIgG4 can be associated with the effect of blocking IgEbinding to allergens and immune response modification (26,30,31). These results are in line with the immunologic and skin prick test outcomes observed in previous studies with DPT 100% (Allergovac® depot, ROXALL Medicina España S.A., Zamudio, Spain) (22,25).…”
Section: A N U S C P R I T a C C E P T E D F O R P U B B L I C A T supporting
confidence: 90%
“…This depot formulation induced an early immunological response, confirmed by statistically significant increments of sIgG and sIgG4 levels against DPT and DF, after approximately 3 months of therapy. Similar results could be observed in other studies, where a fast increase in sIgG and sIgG4 can be associated with the effect of blocking IgEbinding to allergens and immune response modification (26,30,31). These results are in line with the immunologic and skin prick test outcomes observed in previous studies with DPT 100% (Allergovac® depot, ROXALL Medicina España S.A., Zamudio, Spain) (22,25).…”
Section: A N U S C P R I T a C C E P T E D F O R P U B B L I C A T supporting
confidence: 90%
“…The use of whole allergen could present the inconvenience of being recognized by specific IgE and then induce asthma rather than treating it. Several studies have already shown the clinical efficacy and safety of allergen-modified extract (allergoids) in asthma (44)(45)(46)(47). Both allergoids and allergen-derived peptides induce Treg and IL-10secreting DCs to reestablish a tolerance defect (48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…During processing steps, MCT is either coprecipitated with the candidate Ag or the Ag is adsorbed to the preformed MCT. MCT products are marketed for use in AIT, some of which are licensed ( 15 ), and MCT has been shown to facilitate allergen-specific IgG4 Ab production as well as IL-10 secretion from T cells ( 16 19 ). This study compares MCT and alum in mouse models to better understand their mode of action as adjuvants in AIT and other vaccines.…”
Section: Introductionmentioning
confidence: 99%